Effect of Rotational Pokkali cultivation and Shrimp farming on the Soil Characteristics of two different Pokkali field at Chellanam and Kadamakudi, Kochi, Kerala, INDIA - Ashamol Antony, T.V.Anna Mercy and Shaju S.S (International Research Journal of Environment Sciences, 2014)
Pokkali field is prevalent in the coastal saline tracts of Kerala. Pokkali fields are able to produce paddy and shrimp rotationally in an organic way. The sediment characteristics were studied in two Pokkali fields, Chellanam and Kadamakudi, Ernakulam District, Kerala, India during April to June 2013. The soil pH varied highly acidic to7.15 slightly alkaline in Chellanam and alkaline in Kadamakudi. The least value of conductivity and salinity were occurred on the first half of the June.The highest value of total organic carbon was 1.05%in Chellanam and 6.225% in Kadamakudi observed on the second half of April. The highest value of phosphate was 0.1578 mg/g in Chellanam and 0.2125 mg/g in Kadamakudi with a mean and standard deviation of 6.87 ± 7.67 and 0.14 ± 0.05 respectively on the first half of the May. The nitrogen content of the soil also showed the same trend as phosphate. The carbon content of the soil showed a slight increasing trend. The sulphur content of the soil is negligible except last half of may showed 0.18% . In Chellanam and Kadamakudi, the sulphur content of the soil showed a decreasing trend from April to June.C – N ratio was in the range of 6.3: 1 to 8.1: 1. C- N ratio in Chellanam and in Kadamakudi was in the range of 9: 1 to 10.2: 1. The sediment characteristics in this area were completely depends on the south west monsoon and the tides of the Vembanad estuary.